2011
DOI: 10.1245/s10434-011-2036-1
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Features on Rectal MRI Identify a High-risk Group that May Benefit from More Intensive Preoperative Staging and Treatment

Abstract: Adverse features found on rectal MRI identify patients at increased risk of synchronous metastatic disease. This group may benefit from additional preoperative investigation for synchronous metastases such as FDG-PET/CT or liver MRI and from alternative neoadjuvant chemotherapy regimens including induction chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 24 publications
1
52
0
1
Order By: Relevance
“…Six articles (Smith et al , 2008; Hunter et al , 2012; Bugg et al , 2014; Sohn et al , 2014; Seehaus et al , 2015; Chand et al , 2015) reporting on metastatic disease in patients with rectal cancer and EMVI that were retrieved from the electronic databases met the inclusion criteria (Supplementary Table 1). Two studies were from the same centre but evaluated different time cohorts (Smith et al , 2008; Chand et al , 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six articles (Smith et al , 2008; Hunter et al , 2012; Bugg et al , 2014; Sohn et al , 2014; Seehaus et al , 2015; Chand et al , 2015) reporting on metastatic disease in patients with rectal cancer and EMVI that were retrieved from the electronic databases met the inclusion criteria (Supplementary Table 1). Two studies were from the same centre but evaluated different time cohorts (Smith et al , 2008; Chand et al , 2015).…”
Section: Resultsmentioning
confidence: 99%
“…By comparing pre and post-treatment scans, magnetic resonance imaging (MRI) identifies the persistence of EMVI in a greater percentage of patients than histopathology (mrEMVI; Chand et al , 2015) and has a high sensitivity even when enhanced histopathological techniques are used (Jhaveri et al , 2016). Several studies have reported the prevalence of mrEMVI and its correlation to the development of metastatic disease (Smith et al , 2008; Hunter et al , 2012; Bugg et al , 2014; Sohn et al , 2014; Seehaus et al , 2015; Chand et al , 2015; Kim et al , 2016). Given the standardised, reproducible and prognostically validated methods of describing tumour using MRI, it is considered a standard for preoperative risk stratification and treatment decision-making (Brown et al , 2003; Ernst-Stecken et al , 2004; Mercury Study Group, 2006; Smith et al , 2008; NICE, 2011; Shihab et al , 2011; Taylor et al , 2011, 2014b; Glimelius et al , 2013; Yu et al , 2014; Battersby et al , 2016; National Comprehensive Cancer Network 2015; Chand et al , 2015).…”
mentioning
confidence: 99%
“…The high-resolution MRI allows preoperative identification of EMVI [20]. Hunter et al revealed that certain adverse features, including MRI-detected EMVI, could identify patients at increased risk of synchronous metastatic disease [24]. However, although they used MRI-detected EMVI as one of the possible high risk factors, they did not evaluate it as an independent risk factor for distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that mesorectal vascular and fascia invasion by rectal magnetic resonance imaging (MRI) in rectal cancer patients independently predict early metastases (15,16), and thus, it was suggested that liver MRI should be performed at diagnosis in high risk patients. Recently, a clinical trial (SERENADE) was initiated to determine the usefulness of DW-MRI for screening synchronous liver metastases in high risk primary CRC patients (17).…”
Section: Index Termsmentioning
confidence: 99%